Quality of life of Women Shore Gatherers in Coastal Communities in the Los Lagos Region of Chile - Alex Véliz Burgos; Anita Patricia Dörner Paris; Raquel Pereira Berrios; Alexis Soto Salcedo (Revista Finlay)
Foundation: quality of life plays a fundamental role in the perception of human well-being and constitutes a comprehensive concept that encompasses both physical and emotional well-being.  Objective: to identify the perception of quality of life among women shore harvesters from coastal communities in the Los Lagos Region of Chile.  Methods: a study was conducted in the Los Lagos Region of Chile in 2024. A total of 105,311 people were registered in the artisanal fishing registry, of whom 27,228 were women and 23,097 were registered as shore harvesters. This study is framed within an interpretive qualitative paradigm and utilized grounded theory. The sample consisted of 22 women. Purposive sampling was used, selecting women with more than ten years of experience in shore harvesting. Information was collected through in-depth interviews. Informed consent and the protection of the anonymity of the participants were considered.  Results: women harvesters on the shores of the Reloncaví Sound, Los Lagos Region, experience a quality of life perceived as a holistic state of well-being, profoundly influenced by their connection to their natural environment, the appreciation of their work, and the community dynamics that empower their work.  Conclusions: it is imperative that concerted efforts be made to empower them and recognize their contributions, thereby ensuring the continuity of their practices and the well-being of their communities.